ON THE ORIGIN AND EMERGENCE OF PHILOSOPHY - Berrabah Omar (International Journal of Innovative Technologies in Social Science, 2025)
The question of philosophy and its origin is as old as philosophy itself; yet it is a question that is continually renewed with every shift in cultural centralities or as a sign of transition to a new civilizational cycle. This question reflects the problem of civilizational centrism, which many historians and philosophers articulate in their writing of history and in the production of ideas. In this article, we seek to examine the positions that address the origin of philosophy and endeavor to provide objective responses to this question. The aim is to eliminate manifestations of extremism and to clarify the points of ambiguity that have led to a lack of clarity in addressing this problematic issue.